Bronchopulmonary disposition of IV cefepime/taniborbactam (2–0.5 g) administered over 2 h in healthy adult subjects. (9th January 2023) - Asempa, Tomefa E; Kuti, Joseph L; Nascimento, Jeffrey C; Pope, Samuel J; Salerno, Edward L; Troy, Patrick J; Nicolau, David P
Abstract: Introduction: Taniborbactam (formerly VNRX-5133) is an investigational β-lactamase inhibitor in clinical development in combination with cefepime for the treatment of MDR Gram-negative pathogens. Objectives: To assess the safety profile and pulmonary disposition of 2–0.5 g cefepime/taniborbactam administered as a 2 h IV infusion every 8 h following three doses in healthy adult subjects. Methods: In this Phase 1 trial, open-label study, plasma samples were collected over the last dosing interval, and subjects ( n = 20) were randomized to undergo bronchoalveolar lavage (BAL) at four timepoints after the last dose. Drug concentrations in plasma (total and free as determined by protein binding), BAL fluid and alveolar macrophages (AM) were determined by LC-MS/MS, and the urea correction method was used to calculate epithelial lining fluid (ELF) drug concentrations. Pharmacokinetic parameters were estimated by non-compartmental analysis. Results: Mean (±SD) taniborbactam C max and AUC0–8 in plasma were 24.1 ± 4.1 mg/L and 81.9 ± 13.9 mg·h/L, respectively. Corresponding values for cefepime were 118.4 ± 29.7 mg/L and 346.7 ± 71.3 mg·h/L. Protein binding was 0% for taniborbactam and 22.4% for cefepime. Mean taniborbactam concentrations (mg/L) at 2, 4, 6 and 8 h were 3.9, 1.9, 1.0 and 0.3 in ELF and 12.4, 11.5, 14.3 and 14.9 in AM, with corresponding AUC0–8 ELF of 13.8 and AUC0–8 AM of 106.0 mg·h/L. Cefepime AUC0–8 ELF was 77.9 mg·h/L. No serious adverse events were observed. Conclusion: The observed bronchopulmonary exposures of taniborbactam and cefepime can be employed to design optimal dosing regimens for clinical trials in patients with pneumonia.